Extratropical Shortwave Cloud Feedbacks in the Context of the Global Circulation and Hydrological Cycle. Issue 8 (26th April 2022) - McCoy, Daniel T.; Field, Paul; Frazer, Michelle E.; Zelinka, Mark D.; Elsaesser, Gregory S.; Mülmenstädt, Johannes; Tan, Ivy; Myers, Timothy A.; Lebo, Zachary J.
Abstract: Shortwave (SW) cloud feedback (SWFB ) is the primary driver of uncertainty in the effective climate sensitivity (ECS) predicted by global climate models (GCMs). ECS for several GCMs participating in the sixth assessment report exceed 5K, above the fifth assessment report "likely" maximum (4.5K) due to extratropical SWFB 's that are more positive than those simulated in the previous generation of GCMs. Here we show that across 57 GCMs Southern Ocean SWFB can be predicted from the sensitivity of column‐integrated liquid water mass (LWP) to moisture convergence and to surface temperature. The response of LWP to moisture convergence and the response of albedo to LWP anti‐correlate across GCMs. This is because GCMs that simulate a larger response of LWP to moisture convergence tend to have higher mean‐state LWPs, which reduces the impact of additional LWP on albedo. Observational constraints suggest a modestly negative Southern Ocean SWFB — inconsistent with extreme ECS. Plain Language Summary: As the climate warms, moisture convergence into the extratropics strengthens, increasing cloudiness, reflected sunlight, and precipitation. Increased cloudiness in response to moisture convergence is affected by how efficiently clouds condense from water vapor relative to how efficiently precipitation depletes them. Simulations where clouds form efficiently cannot reflect much more sunlight in the extratropics because they are already very cloudy and bright. Observations constrain both the sensitivity of reflected sunlight to cloud and of cloud to moisture. Combining these constraints with constraints on other cloud regimes rules out extremely small and large future warming. Key Points: Enhanced moisture convergence with warming creates a negative extratropical cloud feedback Cloud source and sink efficiency set the extratropical cloud response Constraint by observations suggests a weakly negative feedback‐ and a moderate effective climate sensitivity